Kaiso mainly locates in the nucleus in vivo and binds to methylated, but not hydroxymethylated DNA - Qin, Sisi; Zhang, Baozhen; Tian, Wei; Gu, Liankun; Lu, Zheming; Deng, Dajun (Chinese Journal of Cancer Research, 2015)
Objective: Kaiso is upregulated in many cancers and proposed to bind with both methylated- and unmethylated-DNA in the nucleus as a transcriptional repressor. The objective is to define its subcellular localization in vivo and exact binding DNA sequences in cells. Methods: Compartmentalization of exogenous Kaiso in cells was tracked with enhanced green fluorescence protein (EGFP) tag. The endogenous Kaiso expression in gastric carcinoma tissue was examined with immunohistochemical staining. Kaiso-DNA binding was tested using electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation assay (ChIP). Results: Kaiso mainly localized in the nucleus of cancer and stromal cells in vivo, but remained in the cytoplasm of cultured cells. Most importantly, nuclear Kaiso can bind with the methylated-CGCG-containing sequence in the CDKN2A promoter, but not with the hydroxymethylated-CGCG sequence in HCT116 cells. Conclusions: Kaiso locates mainly in the nucleus in vivo where it binds with the methylated-CGCG sequences, but does not bind with the hydroxymethylated-CGCG sequences.